A sensitivity analysis on the parameters affecting large diameter helical pile installation torque, depth and installation power for offshore applications. Issue 3 (2nd September 2018) - Spagnoli, Giovanni; de Hollanda Cavalcanti Tsuha, Cristina; Oreste, Pierpaolo; Mendez Solarte, Carlos Mauricio
Abstract : The potential application of offshore helical pile systems is currently under the attention of the geotechnical community. This paper considers a theoretical analysis of different helical piles with helix-to-shaft ratios (i.e. wing ratio) of 1.5, 2.0 and 2.5 with a constant shaft diameter of 500 mm installed in clays with different undrained shear strength values up to 500kPa and two different sensitivity values. Three different maximum uplift capacity values (10, 15 and 20 MN) have been hypothesised. Two uplift capacity equations have been used and compared among each other to assess the maximum installation depth to reach the required uplift capacity values. Torque assessment has been also performed using two different models. Results show that if sensitivity is considered during the design as a result of pile installation, pile design depths reduce. Torque values tend to reduce too, as the remoulded clay is less resistant. Power assessment has been also obtained from the torque values using the theory of Tresca. A Montecarlo analysis was also performed to show how the uncertainties of the geotechnical parameters influence the installation depth based on the required uplift force.